KEINDAHAN DI BALIK TRAGEDI - I Made Saryana (SURYA SENI, 2007)
The use of transportation facilities represents the metaphor of “double-sides sword”, on the one hand it gives usefulness, on the other hand it gives destruc- tiveness. An ideal dualism of modern culture achievement, and the tragedy in- herently implied. While the comfort of traveling embodies the positive side, the pollution and car accident represent the negative side. We have no other alternative, nevertheless, since the modern culture demanded such a high mobility that the use of modern transportation is unavoidable. Almost everyday we heard and read in mass media about various accident of car crashes. Even in minor cases, the victims or damages are always unavoidable. In a huge scale, the accident of transportation might take a great many victimsand material damages. Consequently, the survivors or the relatives of the casualties might experience mourning and sadness, even trauma. These are what we might call tragedies, the ones causing human suffering.Viewed as an event, accident left at least two realities: the one associated with mental/psychological implication and the other related to the factual objects that create automatically new “meaning”, even transformation to other “meaning”.In my opinion, the wrecked cars, or those with the paint peeled off, or the chassis detached, or the whole body burnt out, represent the factual reality of the objects undergone the transformation of “meaning”. A paradoxical reality ofmeaning: between the one referring to the traumatic side, and the other that signify the visually artistic side. It is on this paradoxical meaning that I based my creative exploration to create my photographic artworks. Observation mightinspire an unexpected visual composition. For example, a vehicle with its fabulous design might experience a sudden crash that creates effects such as dented or broken into pieces, while at the same time it creates something unique or fascinating. Here, I saw “the meaning of the beauty” behind the tragic outcome.  By photographing the most unique and the most interesting of the broken  pieces of the wrecked cars using the close-up function, an artistic and aesthetical photographic artwork might be created. That is the reason for me to choose the title “Beauty behind Tragedy”. Keywords: photographic artworks, tragedy and beauty.